2012
DOI: 10.1007/s11095-012-0725-5
|View full text |Cite
|
Sign up to set email alerts
|

Stability Influences the Biodistribution, Toxicity, and Anti-tumor Activity of Doxorubicin Encapsulated in PEG-PE Micelles in Mice

Abstract: Purpose To investigate the influences of stability of doxorubicin (DOX) retained in PEG-PE/HSPC micelles on its biodistribution, toxicity and anti-tumor activity in mice. Methods We incorporated HSPC into PEG-PE micelles at various molar ratios by a self-assembly procedure. Micelles were characterized by dynamic light scattering, transmission electron microscope, atomic force microscopy. Agarose gel electrophoresis assay was used to detect stable retention of DOX in micellar preparations. Biodistribution, toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
2
14
0
3
Order By: Relevance
“…SPM did not outperform Duopafei in terms of suppressing growth of the primary tumor [39], but dramatically suppressed metastasis, especially in mice with resected primary tumors. The enhanced anti-metastatic efficacy of SPM may be attributed to its lymphatic accumulation associated with its small size and increased delivery to the lymphatic system, which is consistent with previous observations using other kinds of anti-cancer drugs [19-22,24]. …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…SPM did not outperform Duopafei in terms of suppressing growth of the primary tumor [39], but dramatically suppressed metastasis, especially in mice with resected primary tumors. The enhanced anti-metastatic efficacy of SPM may be attributed to its lymphatic accumulation associated with its small size and increased delivery to the lymphatic system, which is consistent with previous observations using other kinds of anti-cancer drugs [19-22,24]. …”
Section: Discussionsupporting
confidence: 89%
“…Preventing or inhibiting lymph node metastasis is thus critical for improving the outcome of BC patients, and the role of the lymphatic system as a major conduit for the proliferation and spread of pathologies, including metastatic BC [16-18], has directed attention on suitable drug-delivery strategies. Smaller nanodrugs (10–30 nm diameter) have recently proven effective against tumor metastasis and their mechanisms can be explained by lymphatic accumulation of these small-sized nanodrugs [19-22]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, we have shown that a number of water-soluble drugs, such as Dox, vinorelbine tartrate and epirubicin hydrochloride, can be effectively incorporated into PEG-PE micelles with high drug-loading efficiency (>99.0%) using a one-step self-assembly method [20,26,27]. This method is very simple, fast and efficient for preparing the drug carriers in aqueous solution without using organic solvents.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of free Dox in filtrate was quantified by reverse-phase HPLC (RP-HPLC, Agilent 1206, USA) with a C 18 column (ZORBAX 300SB-C18, 5 μm, 4.6 × 150 mm, Agilent, USA). The detection wavelength used was 254 nm, and the mobile phase was composed of sodium dodecyl sulfate (SDS) solution (2.88 g of SDS and 1.36 mL of phosphoric acid were co-dissolved in 1000 ml of Milli-Q water)-acetonitrile-methanol (25: 25: 3, v/v/v) at a flow rate of 1.0 ml/min, as previously reported [20]. The concentration of free E5 in filtrate was quantified using spectrophotometer (SpectraMax i3, Molecular Devices, USA).…”
Section: Methodsmentioning
confidence: 99%